Degradation of crude oil and utilization of hydrocarbon compounds by bacterial isolates from used engine oil-contaminated soil and detection of the hydrocarbon-degrading genes - Nicdao, Michael Angelo C.
Two strains of Gordonia species and Gordonia terrae were isolated from soil sample contaminated with engine oil using mineral salt medium (MSM). The samples were obtained from a motor shop in Magalang, Pampanga, Philippines.